ANALISIS KESULITAN BELAJAR MENULIS CERITA NARASI BAHASA JAWA PESERTA DIDIK KELAS V DI SDN SUKOHARJO 01 PATI - Denisa Nurul Fajri; Nur Amalia (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
Research regarding the difficulties of learning to write Javanese narrative stories needs to be carried out because participants may have difficulty learning to write Javanese narrative stories. This research aims to determine (1) the ability of fifth grade students in writing narrative stories in Javanese; (2) form of difficulty learning to write Javanese narrative stories; (3) factors causing difficulties in learning to write Javanese stories. The research method used is a qualitative method. The research results include: (1) students' ability to write Javanese narrative stories is still low; (2) the forms of difficulty experienced by students occur in arranging words according to base language, pronunciation of phonemes and writing words in Javanese, as well as determining punctuation marks and capital letters; (3) The factors causing difficulty in writing narrative stories in Javanese are a lack of interest in learning Javanese and unfamiliarity with using Javanese in everyday life.